Atividade fotocatalítica de nanocompósitos ZnO/Fe3-xMnxO4/óxido de grafeno (0,075≤x≤0,30) obtidos com nanopartículas sintetizadas em meio bioquelante amazônico - Matos, Robert Saraiva (2022)
In this work, ZnO/Fe3-xMnxO4/OG (0.075≤x≤0.30) nanocomposites were obtained using nanoparticles synthesized by a novel green sol-gel route using Brosimum parinariodides sap as a chelating agent. The main goal was to validate the use of sweet Amapá milk as a chelating agent for the synthesis of ZnO and Fe3-xMnxO4 nanoparticles (0.075≤x≤0.30) to obtain magnetic nanocomposites for photocatalytic application. XRD, TEM, and FTIR analyzes confirmed the formation of nanoparticles with hexagonal (ZnO) and cubic (Fe3- xMnxO4 (0.075≤x≤0.30)), monophasic and highly crystalline structures. The teetotum-like (ZnO) and spherical (Fe3-xMnxO4 (0.075≤x≤0.30) morphologies predicted by a theoretical model applied to XRD patterns were confirmed using high-resolution TEM images. These morphologies were also observed in the nanocomposites, but the crystallite and particle size increased significantly. The optical bandgap of the nanoparticles and nanocomposites were influenced by the various structural defects present in the nanoparticles. Fe3-xMnxO4 (0.075≤x≤0.30) nanoparticles and nanocomposites exhibited a weak but persistent ferrimagnetic behavior. Photocatalytic tests showed that the recyclable and reusable nanocomposite ZnO/Fe3-xMnxO4/OG (x = 0.15) was the only sample capable of degrading 100% of the methylene blue dye after 240 min of irradiation with visible light. These findings prove that the obtained nanocomposites are viable for photocatalytic application.